INTEGRASI NILAI-NILAI BUDAYA MELAYU RIAU DALAM PEMBELAJARAN SEBAGAI UPAYA PELESTARIAN BUDAYA PADA PESERTA DIDIK - Farhanaldi, Zaekly; Ilman, Nabil; Simamora, Muhammad Najar; Michola, Airlangga; Sakilah, Sakilah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the integration of Malay cultural values of Riau in learning as an effort to preserve culture and its impact on students’ character development. This research employs a qualitative approach with a literature study design, using data sources from books, journal articles, and relevant previous studies. Data were collected through literature review and analyzed using content analysis techniques. The results show that the integration of Riau Malay cultural values in learning is carried out through the incorporation of values into teaching materials, the use of contextual learning methods, as well as teacher role modeling and habituation. The values integrated include religiosity, politeness, responsibility, cooperation, and respect. This integration not only serves as an effort to preserve local culture but also has a significant impact on students’ character development, such as being religious, disciplined, responsible, socially aware, and having a strong cultural identity. In conclusion, the integration of Riau Malay cultural values in learning is an effective strategy to develop students’ character while preserving local culture in the era of globalization.